A DNA gyrase-binding site at the center of the bacteriophage Mu genome is required for efficient replicative transposition. - Pato, M L (1990)
We have discovered a centrally located site that is required for efficient replication of bacteriophage Mu DNA and identified it as a strong DNA gyrase-binding site. Incubation of Mu DNA with gyrase and enoxacin revealed a cleavage site 18.1 kilobases from the left end of the 37.2-kilobase genome. Two observations indicate a role for the site in Mu replication: mutants of Mu, able to grow on an Escherichia coli gyrB host that does not allow growth of wild-type Mu, were found to possess single-base changes resulting in more efficient gyrase binding and cleavage at the site. Introduction of a 147-base-pair deletion that eliminated the site from a prophage inhibited the onset of Mu replication for greater than 1 hr after induction.